Over Current Relay Coordination System Considering Distributed Generation - Teguh Aryo Nugroho; Muhammad Abdillah; Helmi Fauzan; Nita Indriani Pertiwi; Herlambang Setiadi; Awan Uji Krismanto (Journal of Emerging Supply Chain, Clean Energy, and Process Engineering, 2022)
Today, electricity is one of the important components to drive the industrial process and other daily human activities. While the continuity of power supply through the power system grid is impressionable from disturbances such as a short circuit. In addition, the rapid development of distributed generation (DG) technology triggers the industry to use DG technology to maintain power quality and support for industrial processes. This paper proposed the coordination of over current relay (OCR) considering distributed generation (DG) to provide an extraordinary protection system in an electrical system network. The relay is coordinated with the other relay equipment to enhance the system more reliable, secure, and stable. To examine the efficacy of the proposed approach, the radial distribution system model is utilized in this paper where the DG is installed in bus 6. To compute the protection coordination index (PCI) and coordination time interval (CTI), the DG capacity is varied from 100 KVA to 1000kVA. From the simulation result, it could be seen that the installed DG that allowed in bus 6 was 900kVA because the CTI value reached convergence value as of 0.294 second for higher DC capacity than 900kVA. Moreover, the higher of DG capacity was injected to electrical system, the higher of PCI values was obtained.